Care Trajectories for Yukon Francophone Seniors - De Moissac, Danielle (Parteneriat communauté en santé, 2023)
Over the past several years, the Yukon Government has been exploring the matter of aging in place for its senior citizens (Government of Yukon, 2019). In the 2018 report entitled Yukon Health Status Report – Focus on Seniors, the Government of Yukon (2018) presented a profile of the health and well-being of Yukon seniors. t is important to note, however, that the voice of Francophone seniors is neither represented in the Focus on Seniors report (Government of Yukon, 2018) nor in the public engagement documentation, except for the mention of a liaison service for Francophones when discharged from the hospital (Government of Yukon, 2018 What we Heard About Aging in Place., p. 26). Although Francophones were able to participate in the engagement process, no mention was made about any specific needs of Francophone seniors. In light of the fact that Francophone seniors living in a minority language situation are aging at a proportionally faster rate than the overall Canadian population (Bouchard et al., 2015) and that this results in increased use of home care and other services (Van Kemenade, Bouchard & Bergeron, 2015), the needs of seniors from both of Yukon’s official language groups must be considered. This report provides information to further our understanding of this matter. Report Objectives: 1) To present findings related to Yukon Francophone senior care trajectories, from the moment when they first perceive the need for support with their overall health, on the physical as well as the mental and social levels. 2) To identify the care, health, and social service needs of these seniors, according to the services available, such that the active offer of French language services meets their needs.

Trajectoires de soins pour les aîné(e)es francophones du Yukon - de Moissac, Danielle (Partenariat communauté en santé, 2023)
Le gouvernement du Yukon s’intéresse depuis quelques années à la question du vieillissement chez soi pour sa population aînée (gouvernement du Yukon, 2019). Un rapport publié en 2018 intitulé Yukon Health Status Report: Focus on Seniors (Gouvernement du Yukon, 2018) présente le profil de santé et de mieux-être des aîné·e·s du territoire. Force est de constater, toutefois, que la voix des francophones n’est représentée ni dans le rapport sur la santé des aîné·e·s (Gouvernement du Yukon, 2018) ni dans les écrits émanant des consultations, autrement que par la mention d’un service de liaison pour les francophones à leur congé de l’hôpital (p. 26, Gouvernement du Yukon, 2018 What we Heard About Aging in Place.). Bien que des francophones aient pu participer aux consultations, aucune trace des besoins spécifiques des aîné·e·s de la francophonie n’est rapportée. Sachant que la population aînée francophone vivant en situation linguistique minoritaire vieillit proportionnellement plus rapidement que l’ensemble de la population canadienne (Bouchard et coll., 2015) et que cela engendre une utilisation accrue de soins à domicile et d’autres services (van Kemenade, Bouchard et Bergeron, 2015), il est important de saisir les besoins des personnes âgées issues des deux groupes de langues officielles du Yukon. Ce présent rapport pourra mieux nous informer à cet égard. Objectifs du rapport: 1) Exposer les constats relatifs aux trajectoires de soins pour les aîné·e·s francophones du Yukon, à partir du moment où ils ressentent le besoin de soutien en lien avec leur santé globale, tant physique que mentale et sociale; 2) Prendre connaissance des besoins de ces aîné·e·s quant aux soins et services sociaux et de santé, en relation avec les services disponibles dans une optique d’offre active de services en français qui répondent à leurs besoins.

Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

Exploring Primary Care Physicians’ Experiences of Language and Cultural Discordant Care for Linguistic Minority Patients at the End-of-Life: A Study Protocol - Lee, Seung Heyck; Gibb, Maya; Karunananthan, Sathya; Cody, Margaret; Tanuseputro, Peter; Johnston, Sharon; Kendall, Claire; Bedard, Daniel; Collin, Stéphanie; Kehoe MacLeod, Krystal (International Journal of Qualitative Methods, 2023)
Health disparities exist across different linguistic groups. Language barriers in primary care can negatively affect access to healthcare services and the quality and safety of care at the end-of-life. This study will take a novel, in-depth look at the experience of language- and/or cultural-discordant care for adults from linguistic minority groups through the eyes of primary care physicians providing palliative and/or end-of-life care. Language and cultural discordance means that the physician and patient do not speak the same language or are not from the same cultural background. Qualitative data from primary care physicians (n = 12–24) providing language-discordant end-of-life care to Francophone and/or Allophone older adults across different care models and diverse geographies in Ontario will be collected through semi-structured interviews. Reflexive thematic analysis will be used to report themes within the data and consider the influence of the social locations of the researcher and research participants, geographic considerations impacting service provision, and barriers imposed by differing primary care funding structures on the provision of palliative and end-of-life care for linguistic and cultural minority groups in Ontario. Findings from this study will identify the interconnections among language and cultural discordance, care model, geographic region, and physician perceptions of their combined effects on access to, and quality of, palliative and end-of-life care. This evidence will be key to informing clinical practice guidelines and mobilizing change to improve primary care access and quality for adults at the end-of-life from linguistic and cultural minority populations across Ontario. Keywords: language discordance, qualitative research, reflexive thematic analysis, palliative care, primary care physicians, semi-structured interviews